2018
DOI: 10.1037/per0000249
|View full text |Cite
|
Sign up to set email alerts
|

Using latent variable- and person-centered approaches to examine the role of psychopathic traits in sex offenders.

Abstract: The current study employed both latent variable- and person-centered approaches to examine psychopathic traits in a large sample of sex offenders (N = 958). The offenders, who had committed a range of sexual crimes, had been assessed with the Psychopathy Checklist-Revised (PCL-R; Hare, 2003). Structural equation modeling results indicated that the four-factor model of psychopathy (Hare, 2003; Neumann, Hare, & Newman, 2007) provided good representation of the dimensional nature of psychopathic traits across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
43
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 60 publications
19
43
0
9
Order By: Relevance
“…In the first part, we used LPA with a complete sample of violent offenders to determine if a manifest psychopathic subtype could be differentiated from other offender subtypes. Based on the theoretical literature and previous empirical findings (7, 25), we expected to find four viable latent classes (or profiles) of PCL-R facet scores. In accordance with the findings from North American and Swedish samples of adult male offenders (5, 7), we expected to find a class indicative of primary psychopathy with high average scores on all four PCL-R factors, a sociopathic class with low average scores on Factor 1 and high average scores on Factor 2, a class indicative of callous-conning offenders (with high average scores on Factor 1 and low average scores on Factor 2), and a general offender class with average low scores on all factors.…”
Section: Purpose Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the first part, we used LPA with a complete sample of violent offenders to determine if a manifest psychopathic subtype could be differentiated from other offender subtypes. Based on the theoretical literature and previous empirical findings (7, 25), we expected to find four viable latent classes (or profiles) of PCL-R facet scores. In accordance with the findings from North American and Swedish samples of adult male offenders (5, 7), we expected to find a class indicative of primary psychopathy with high average scores on all four PCL-R factors, a sociopathic class with low average scores on Factor 1 and high average scores on Factor 2, a class indicative of callous-conning offenders (with high average scores on Factor 1 and low average scores on Factor 2), and a general offender class with average low scores on all factors.…”
Section: Purpose Of This Studymentioning
confidence: 99%
“…Here, Neumann et al (7) as well as Krstic et al (25) used total, unselected offender samples and identified four subtypes: prototypic (high scores on all four facets), callous-conning (elevated Interpersonal and Affective facet scores), sociopathic (elevated Lifestyle and Antisocial facet scores), and general offender (relatively low scores on all four facets). Validation analyses by Krstic et al (25) using offense behavior showed prototypic subtype offenders to be more violent in the commission of their sexual crimes (compared to all other three subtypes) and general offenders to engage in more sexual behavior (compared to sociopathic offenders). These results indicate that the use of a total sample provides evidence of a range of subtypes, which may also vary considerably in their recidivism risk, criminogenic needs, and response to treatment.…”
mentioning
confidence: 99%
“…All three of these traits are relevant for explaining youth (e.g., Sitney, Caldwell & Caldwell, 2016) and adult (e.g. Krstic et al, 2017;Shepherd, Campbell & Ogloff, 2016) offending behaviour. However, not all societal problems are criminal in nature and risk-taking in financial, health and recreational domains may also lead to negative social consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of externalizing behavior, psychopathy is also associated with deviant sexual behavior (Krstic et al, 2018;Mokros, Osterheider, Hucker, & Nitschke, 2011;Muñoz, Khan, & Cordwell, 2011;Williams et al, 2009;Woodworth et al, 2013), although the association between psychopathy and deviant sexuality has been relatively understudied so far and also has produced mixed findings (Garofalo, Bogaerts, & Denissen, 2018). Nevertheless, theories of sexual offending often highlight the role of psychopathic traits in the manifestation of deviant sexual interests and behavior and the assessment of psychopathy is recommended when dealing with sexual deviance as an integral part of treatment planning (Laws & O'Donohue, 2008;Stinson, Sales, & Becker, 2008).…”
mentioning
confidence: 99%